Efektivitas Efektivitas Prosedur Beracara Perkara Gugatan Sederhana di Pengadilan Agama Sukadana - Febrianti, Jesica; Nizaruddin; Putri, Shely Nasya (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2025)
The number of simple lawsuit cases filed in the Religious Court is very rare and minimal. This study discusses the factors behind the rarity of simple lawsuit cases and solutions to address this scarcity. The research uses a qualitative approach, with data sources obtained from interviews and documentation. The findings show that simple lawsuits at the Sukadana Religious Court are rare, with only 4 cases recorded between 2019 and 2022, and none in 2023-2024. The Religious Court has always kept up with the latest regulations on simple lawsuits, specifically the Supreme Court Regulation (Perma) No. 2 of 2015, as amended by Perma No. 4 of 2019. This regulation has been effective in handling simple lawsuit cases, but the lack of information provided to the public is one of the reasons for the scarcity, even the complete absence, of such cases at the Sukadana Religious Court. This paper highlights the importance of providing information to the public so that they understand how to seek justice regarding simple lawsuits in the religious court.